Urogynaecology Training in South East Asia (SEA) and Asia - Ng Kwok Weng Roy (Majalah Obstetri dan Ginekologi, 2019)
South East Asia (SEA) is made up of 11 countries (Viet-nam, Laos, Cambodia, Thailand, Myanmar, Malaysia, Singapore, Brunei, Philippines, Indonesia and Timor Leste) from Myanmar in the northwest to Timor Leste in the far south east. It is one of the most far flung region in Asia, with a land mass of 4.5 million km2 and theitspopulation of 641 million makes it the third most populous geographical region in the world after South Asia and East Asia. Asia is the world’s largest most populous continent stretching from the Middle East in the west to Japan in the east with a population of 4.567 billion.